PSYCHOLOGICAL IMPACTS OF ALZHEIMER’S DISEASE AND POSSIBILITIES FOR REHABILITATION - Cristiane Fragoso dos Santos, Quelen; Trevisol, Matias (Health and Society, 2025)
The impacts resulting from Alzheimer’s Disease characterize the loss of progressive cognitive functions, memory, language and learning failures, which, over time, tend to worsen as the disease progresses. Rehabilitation possibilities seek to improve the worsening of the disease, seeking an approach that integrates knowledge in the period (2010 - 2020), in medicine, neurology and psychology. Objective: to carry out a literature review on the impacts and possibilities of rehabilitation of Alzheimer’s disease. Method: searches were performed from April to September 2021, in the following databases: SciELO and PepsiCo, observing the publication date and whether the text was in accordance with the search theme. Results: Ten articles were found that highlighted the impacts and possibilities of rehabilitation of Alzheimer’s disease, in which it was evident how important it is still to research the subject.